Analisis Risiko Operasional Berbasis Pendekatan Enterprise Risk Management Pada Usaha Thrift Online Yodhsi Fashion Cirebon - Maria Olivia Pasaribu; Yesha Artika Galy; Nurul Pratiwi; Putri Kemala Dewi Lubis; Rossy Pratiwi Sihombing (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The Thrifting Shop has become one of the Small and Medium Enterprises (SMEs) that have experienced significant development over the past few years. The current era of globalization has led to consumer behavior influencing the lives of the general public. This is influenced by changing habits and lifestyles. This behavior requires a larger budget, as it is no longer just about meeting needs but also about satisfying desires. Currently, there is a trend towards second-hand clothing (fashion thrift) to meet the increasing demand of consumers, considering that times have changed, buying second-hand clothes has become a trend and a lifestyle that is growing rapidly in Indonesia. Therefore, many new business owners are trying to venture into this thrift business through online platforms like live e-commerce. When discussing the sustainability of a business, it is undeniable that it will face risks. These risks are not only caused by internal factors but also by external factors that force us to be more vigilant in facing these risks. These risks do not only appear in large businesses but also in small-scale businesses like SMEs. This study aims to identify operational risks, their causes, and their impact on business activities and find solutions to address operational risks that occur. The research object is Yodshi Fashion, which is one of the online thrift stores in Cirebon. This study uses a qualitative method with data collection techniques through online observation and interviews with business owners, as well as an analysis based on Enterprise Risk Management (ERM). The research results show that there are operational risks, such as the mismatch between the quality of clothes and stock with customer demand, fluctuations in live traffic on e-commerce, high administrative costs on e-commerce, intense competition among online thrift sellers, a large number of PHP customers during live sales, and the cancellation of COD orders by customers. These risks include internal and external operational risks with a high risk level that occurs in Yodshi Fashion Cirebon. These operational risks can affect the quality of products presented and disrupt the service process for customers. Risk management is crucial for operational activities to minimize and prevent the possibility of risks that can cause losses for Yodshi Fashion Cirebon.